Knowing how essays on knowledge, mind, and action - Bengson, John.; Moffett, Marc A. (New York ; Oxford : Oxford University Press, 2011)
This volume contains fifteen state of the art essays by leading figures in philosophy and linguistics that amplify and sharpen the debate between 'intellectualists' and 'anti-intellectualists' about mind and action, highlighting the conceptual, empirical, and linguistic issues that motivate and sustain the conflict.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Knowledge, Theory of; Act (Philosophy)